Comparative genomics of Gossypium and Arabidopsis: Unraveling the consequences of both ancient and recent polyploidy - Rong, Junkang; Bowers, John E.; Schulze, Stefan R.; Waghmare, Vijay N.; Rogers, Carl J.; Pierce, Gary J.; Zhang, Hua; Estill, James C.; Paterson, Andrew H. (Genome Research, 2005)
Both ancient and recent polyploidy, together with post-polyploidization loss of many duplicated gene copies, complicates angiosperm comparative genomics. To explore an approach by which these challenges might be mitigated, genetic maps of extant diploid and tetraploid cottons (Gossypium spp.) were used to infer the approximate order of 3016 loci along the chromosomes of their hypothetical common ancestor. The inferred Gossypium gene order corresponded more closely than the original maps did to a similarly inferred ancestral gene order predating an independent paleopolyploidization (α) in Arabidopsis. At least 59% of the cotton map and 53% of the Arabidopsis transcriptome showed correspondence in multilocus gene arrangements based on one or both of two software packages (CrimeStatII, FISH). Genomic regions in which chromosome structural rearrangement has been rapid (obscuring gene order correspondence) have also been subject to greater divergence of individual gene sequences. About 26%-44% of corresponding regions involved multiple Arabidopsis or cotton chromosomes, in some cases consistent with known, more ancient, duplications. The genomic distributions of multiple-locus probes provided early insight into the consequences for chromosome structure of an ancient large-scale duplication in cotton. Inferences that mitigate the consequences of ancient duplications improve leveraging of genomic information for model organisms in the study of more complex genomes.
10.1101/gr.3907305